Response to Heethoff, Norton, and Raspotnig: Ant and Mite Diversity Drives Toxin Variation in the Little Devil Poison Frog and Erratum - McGugan, Jenna R. (2016)
Our recent publication titled "Ant and Mite Diversity Drives Toxin Variation in the Little Devil Poison Frog" aimed to describe how variation in diet contributes to population differences in toxin profiles of poison frogs. Some poison frogs (Family Dendrobatidae) sequester alkaloid toxins from their arthropod diet, which is composed mainly of ants and mites. Our publication demonstrated that arthropods from the stomach contents of three different frog populations were diverse in both chemistry and species composition. To make progress towards understanding this trophic relationship, our main goal was to identify alkaloids that are found in either ants or mites. With the remaining samples that were not used for chemical analysis, we attempted to identify the arthropods using DNA barcoding of cytochrome oxidase 1 (CO1). The critique of Heethoff, Norton, and Raspotnig refers to the genetic analysis of a small number of mites. Here, we respond to the general argument of the critique as well as other minor issues detailed by Heethoff, Norton, and Raspotnig